1994
DOI: 10.1016/s0040-4020(01)85267-4
|View full text |Cite
|
Sign up to set email alerts
|

Dealkylation of quaternary ammonium salts by thiolate anions: A model of the cobalamin-independent methionine synthase reaction.

Abstract: Dealkylation of quaternary ammonium salts by thiolate anions: A model of the cobalaminindependent methionine synthase reaction. Hilhorst, E.; Chen, T.B.R.A.; Iskander, A.S.; Pandit, U.K. Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, the Library will make the material inaccessible and/or remove it from the website. Please Ask t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 9 publications
(1 reference statement)
1
27
0
Order By: Relevance
“…Photolysis of the quaternary ammonium bromide 3e ‐Br − with Ar 1 =Ar 2 =Ph67 in CH 2 Cl 2 did not give rise to any absorbance of the benzhydryl cation (Ph 2 CH + ). This is not surprising because the Br − anion undergoes a diffusion‐controlled reaction with Ph 2 CH + ,48 and in CH 2 Cl 2 , the Br − anion would presumably form contact ion pairs with the ammonium ions, i.e., it can intercept the carbocation within the geminate solvent cage.…”
Section: Resultsmentioning
confidence: 93%
“…Photolysis of the quaternary ammonium bromide 3e ‐Br − with Ar 1 =Ar 2 =Ph67 in CH 2 Cl 2 did not give rise to any absorbance of the benzhydryl cation (Ph 2 CH + ). This is not surprising because the Br − anion undergoes a diffusion‐controlled reaction with Ph 2 CH + ,48 and in CH 2 Cl 2 , the Br − anion would presumably form contact ion pairs with the ammonium ions, i.e., it can intercept the carbocation within the geminate solvent cage.…”
Section: Resultsmentioning
confidence: 93%
“…In the MetE enzyme, where the transfer takes place directly to homocysteine, the currently accepted proposal 17 is that the N (5)-protonated ammonium salt 55 is the actual substrate for this transfer. Dicationic electrophiles have never been proposed as intermediates in that reaction, 18 but would a dication be a reasonable intermediate? It is known that tetrahydrofolates are easily oxidized structures, 19 and recent cyclic voltammetry studies on the closely related tetrahydrobiopterin 58 , 19 have shown a single two-electron wave in a reversible oxidation, implying that the second electron is transferred as easily or more easily than the first.…”
Section: Resultsmentioning
confidence: 99%
“…S-[Methyl-d 3 ]methionine was synthesized as described previously (Hilhorst et al, 1994). Homocysteine (500 mg) and 1,8-diazabicyclo[5,4,0]-7-undecene (2 ml) were dissolved into acetonitrile (50 ml).…”
Section: Feeding Experiments With D 3 -Methionine-enriched Dietsmentioning
confidence: 99%